Personalized Reminders: Evidence from a Field Experiment with Voluntary Retirement Savings in Colombia - Jared Gars; Laura Prada; Santiago Borda; Egon Tripodi (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
A large share of the global workforce lacks access to employer-sponsored retire- ment plans. In Colombia, where labor informality is high, the government introduced the Beneficios Económicos Periódicos (BEPS) program to promote voluntary retirement savings. However, many enrollees fail to contribute regularly. We conduct a randomized controlled trial with 2,819 BEPS users, assigning them to different planning and monthly reminder treatments, where reminders are tailored in their timing. We find that personalized reminders significantly increase both the frequency and amount of savings, with individuals who recognize their forgetfulness more likely to demand reminders. Our findings highlight the role of reminders tailored to individuals' preferred timing in sustaining engagement in voluntary savings programs.
Keywords: D91; G41; O16; 330; Retirement savings; personalized reminders; limited attention; financial inclusion